PRODUKTIVITAS DAN KUALITAS SAGU PADA PROSES PENGOLAHAN SECARA MEKANIS DAN SEMI MEKANIS DAN SEMI MEKANIS DI KEC. MERBAU KAB. KEPULAUAN MERANTI - Nusaibah, Nusaibah; Suhesti, Eni; Ratnaningsih, Ambar Tri (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
This research is raining to process processes, calculate and analyze process and mechanical quality and analysis during mechanical and semi-mechanical processes. Research location in CV. Malibur Indah, CV. Kulim Jaya Refinery, Kec. Merbau, Kab. Meranti Archipelago and Faculty of Forestry Laboratory, Lancang Kuning University. This research is done by looking at the production process, deadlock data, data generation, and physical data. Data were analyzed descriptively. Processing of sago in mechanical and semi-mechanical processing consists of raw material preparation, dissolution, starch extraction, precipitation, drying and packing. At stage production of flour production machine for 35 hours, workforce 26 people, product amount 7.5 tons and product produced 7 tons. While the semi-mechanical processing of the production process lasts for 32 hours, labor 10 people, the number of products 1 ton and the product produced 750 kg. Physical quality on mechanical processing ie moisture content of 15.62%, ash content of 0.408% and fineness of flour by 90.23%. While in semi-mechanical processing that the air content of 17.63%, ash content of 0.385%, and flour refinement of 81.17%. Organoleptic test results use more mechanical processing by panelists on texture, while in semi-mechanical processes more panels on color and aroma.